Dihaloimidazolidinediones as Versatile Halodehydrating Agents. Issue 42 (8th August 2014) - Moerdyk, Jonathan P.; Bielawski, Christopher W.
Abstract: Dihaloimidazolidinediones containing geminal dibromides, dichlorides, or diiodides were synthesized and used to transform various alcohols to their corresponding alkyl halides in high yields and under mild conditions. High functional group tolerance and, in many cases, high selectivities were observed. Efforts toward elucidating the mechanism revealed that significant charge build‐up may occur at the eventual halogen containing carbon nucleus prior to substitution. Abstract : X‐Caliber : A series of dihaloimidazolidinediones were synthesized and found to facilitate the halodehydration of various alcohols to the corresponding alkyl halides R‐X (X=Cl, Br, I). The corresponding reactions were found to proceed under mild conditions and tolerated a wide range of functional groups (see scheme). Mechanistic details are also discussed.